Chitosan-, Alginate- Carrageenan-Derived Oligosaccharides Stimulate Defense Against Biotic and Abiotic Stresses, and Growth in Plants: A Historical Perspective - Moenne-Munoz, A; Gonzalez-Figueroa, A (Elsevier Ltd, 2021)
During the last 20 years, the mechanisms involved in the stimulation of defense against pathogens, and growth triggered by chitosan-, alginate- and carrageenan-derived oligosaccharides have been studied in plants. Oligo-chitosan stimulate protection against pathogens by activation of salicylic acid (SA) or jasmonic acid/ethylene (JA/ET)-dependent pathways, protection against abiotic stress through abscisic acid (ABA)-dependent pathway, and growth by increasing photosynthesis, auxin and gibberellin content, C and N assimilation, and synthesis of secondary metabolites with antipathogenic and medicinal properties. Oligo-alginates stimulate protection against pathogens through SA-dependent pathway, abiotic stress via ABA-dependent pathway, and growth by increasing photosynthesis, auxin and gibberellins contents, C and N assimilation, and synthesis of secondary metabolites with antipathogenic and medicinal properties. Oligo-carrageenan increased protection against pathogens through JA/ET, SA- and Target of Rapamycin (TOR)-dependent pathways, and growth by activation of TOR-dependent pathway leading to an increase in expression of genes involved in photosynthesis, C, N, S assimilation, and enzymes that synthesize phenolic compounds and terpenes having antipathogenic activities. Thus, the latter oligosaccharides induce similar biological effects, but through different signaling pathways in plants. © 2021